PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN MINAT BELAJAR SISWA DALAM MATA PELAJARAN PAI PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 004 SUNGAI MANAU KECAMATAN KUANTAN MUDIK - Ulpa Mutiara Asi; Bustanur Bustanur; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The aim of the writer doing research is to know the method Talking Stick learning and increasing interest in learning grade IV students in PAI learning at SDN 004 Sungai Manau. From the results of the initial observations that the author carried out in class IV,. In the learning process, it turned out that there were no teachers applying learning methods to attract student attention more eager to learn, using the lecture method the students will tends to be stiff and bored when the learning process takes place and still is there are also students who come in and out when the teacher explains the lesson. As the subjects in this study were all 16 grade IV students consisting of 7 boys and 9 girls. While the object is the application of the Talking Stick learning method to increasw sudent interest in learning in Islamic Education for grade IV SDN Negeri 004 Sungai Manau. Based on the results collection by means of observation, interviews, and documentation, the analyzed using graphs can be councluded: Application Talking Stick method to increase students interest in learning in the eye PAI lesson for fourth grade student of state Elementary School 004 Sungai Manau District can increase student interest in learnig. This matter proven in the Pre-cycle student interest in learning only 55.2%, in cycle I interest learning increased to 70,9%, in cycle II interest in learning rose to 83,75% and in cycle III students interest in learning reached 97,5%.